The Effect of Foreign Direct And Portfolio Investments on Stock Market Returns in E7 Countries - Topaloğlu, Emre Esat; Şahin, Serkan; Ege, İlhan (Muhasebe ve Finansman Dergisi, 2019)
As a result of financial liberalization boundaries between financial markets have been disappeared and capital movements have accelerated which leads to rise of financial flows from developed to developing countries. Foreign investments can be realized as foreign direct investments indicating the ownership of physical assets in another country or as portfolio investments in assets for the sake of maximum return at minimum risk. The aim of this paper is to investigate the effects of foreign direct and portfolio investments on stock returns in E7 countries (Brazil, China, Indonesia, India, Mexico, Russia, Turkey) for the time period from 2005 to 2016 using panel data analysis. Results indicate a significant and positive relation between foreign portfolio investments and stock market returns whereas a negative relation between foreign direct investment and stock market returns. It is concluded that foreign portfolio investments have very crucial effect in increasing the stock returns in E7 countries.
Keywords: Foreign Direct Investment; Portfolio Investment; Stock Returns; E7 Countries; Panel Data Analysis; Jel Cla